ANALISIS SIKAP KERJA KARYAWAN PERBANKAN SYARIAH BERDASARKAN KARAKTERISTIK BIOGRAFIS - Siswanto Muhammad, Sulhan (lp2m-uin malang, 2011)
The purpose of this study is to compare job satisfaction and organizational commitment of employee’s Islamic banking based on biographical characteristics. Biographical characteristics are consists of age, gender, marital status, and education. Total sample in the research are 125 respondents. Data analysis is executed by independent samples t-test and Analysis of Varians (Anova) with SPSS 16 version. Based on the research indicate that employee job satisfaction is quitely different between men and women. Organizational commitment based on gender is quietly different too. Job satisfaction and organizational commitment of men are higher than women. Managerial implications of human resource management requires to enhance an organizational commitment and job satisfaction of Islamic banking women employeesKeywords: Satisfaction, Organizational Commitment, Islamic Bank